Cybersecurity and medical devices: A practical guide for cardiac electrophysiologists. Issue 8 (12th July 2017) - Ransford, Benjamin; Kramer, Daniel B.; Foo Kune, Denis; Auto de Medeiros, Julio; Yan, Chen; Xu, Wenyuan; Crawford, Thomas; Fu, Kevin
Abstract: Medical devices increasingly depend on software. While this expands the ability of devices to perform key therapeutic and diagnostic functions, reliance on software inevitably causes exposure to hazards of security vulnerabilities. This article uses a recent high‐profile case example to outline a proactive approach to security awareness that incorporates a scientific, risk‐based analysis of security concerns that supports ongoing discussions with patients about their medical devices.